Natural product 1,2,3,4,6-penta-O-galloyl-β-D-glucopyranose is a reversible inhibitor of glyceraldehyde 3-phosphate dehydrogenase - Li Wen; Liao Li-ping; Song Ning; Liu Yan-jun; Ding Yi-luan; Zhang Yuan-yuan; Zhou Xiao-ru; Sun Zhong-ya; Xiao Sen-hao; Wang Hong-bo; Lu Jing; Zhang Nai-xia; et al. (Acta Pharmacologica Sinica, 2022)
Aerobic glycolysis, also known as the Warburg effect, is a hallmark of cancer cell glucose metabolism and plays a crucial role in the activation of various types of immune cells. Glyceraldehyde 3-phosphate dehydrogenase (GAPDH) catalyzes the conversion of D-glyceraldehyde 3-phosphate to D-glycerate 1,3-bisphosphate in the 6th critical step in glycolysis. GAPDH exerts metabolic flux control during aerobic glycolysis and therefore is an attractive therapeutic target for cancer and autoimmune diseases. Recently, GAPDH inhibitors were reported to function through common suicide inactivation by covalent binding to the cysteine catalytic residue of GAPDH. Herein, by developing a high-throughput enzymatic screening assay, we discovered that the natural product 1,2,3,4,6-penta-O-galloyl-β-D-glucopyranose (PGG) is an inhibitor of GAPDH with Ki = 0.5 μM. PGG blocks GAPDH activity by a reversible and NAD+ and Pi competitive mechanism, suggesting that it represents a novel class of GAPDH inhibitors. In-depth hydrogen deuterium exchange mass spectrometry (HDX-MS) analysis revealed that PGG binds to a region that disrupts NAD+ and inorganic phosphate binding, resulting in a distal conformational change at the GAPDH tetramer interface. In addition, structural modeling analysis indicated that PGG probably reversibly binds to the center pocket of GAPDH. Moreover, PGG inhibits LPS- stimulated macrophage activation by specific downregulation of GAPDH-dependent glucose consumption and lactate production. In summary, PGG represents a novel class of GAPDH inhibitors that probably reversibly binds to the center pocket of GAPDH. Our study sheds new light on factors for designing a more potent and specific inhibitor of GAPDH for future therapeutic applications.